Utilization Of Social Network Analysis To Analysis Content Beauty Influencer On The Twitter Application - Tinah, Tinah; Ambarwati, Rita; Indayani, Lilik (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research Aim: This research was conducted to determine the interaction analysis of Beauty Influencer social networks on Twitter users who focused on beauty influencers. Design/Method/Approach: This type of research was qualitative descriptive with the SNA method. Researchers use secondary data from Twitter—data collection techniques through data collection techniques, data preprocessing, analysis, and data visualization. Research Finding: The results show that beauty influencers are connections with nodes that can build social networks between influencers and audiences. Theoretical Contribution/Originality: This study's contributions can be used as a marketing strategy to increase the beauty business's competitiveness. Practitioner/Policy Implication: The implication is to increase brand awareness because they get exposure from influencer followers, build audience trust in products, and increase sales. Research Limitation: Further research on beauty influencer content should be conducted with different and more complete methods.